Bentuk dan Intensitas Edukasi yang Diinginkan Penderita Hipertensi di Jatinangor - Muhammad Rizki Fadil; Yulia Sofiatin; Hanna Goenawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension contributes to numerous complications such as heart disease, stroke, kidney failure, and is a risk factor of disability and death. Hypertension Prevalence in Jatinangor is 37.8%, that is higher than national rate. The control of hypertension is low and the education at the primary health facility is short. Therefore, another buffer system for education such as posbindu is needed. Activities that educate people with hypertension become very important, but need to be adjusted as needs. Aim of this study is to determine form and intensity of education preferred by hypertension patients Method: Qualitative descriptive with case study approach using focused group discussion (FGD) method, led by main moderator and assisted by a second moderator. Participants consisted of 15 people with hypertension chosen purposively with the inclusion criterias female and parallel to the research objective. The discussion used semi-structured questions. This study is conducted in two villages in Jatinangor, Desa Cipacing and Desa Cilayung from February to May 2017. Results: Participants wanted education in the form of traditional learning, game simulation, written notes, and video recording. The intensity of education preferred until patients understand, it tends to be performed more than once, and preferred place are performed within Posyandu (Integrated Health and Nutrition Post) with education frequency varies from once a week to once a month. Conclusion: Hypertension patients have variable preference of education forms and its intensity. Innovations in the development of methods in accordance with hypertension patients’ needs must be continued, so that interventions can become more effective for hypertension patients.